Pendampingan Penggunaan Writing Tools dalam Peningkatan Karya Tulis Mahasantri Pondok Pesantren Sunan Drajat Lamongan - Ulum, Miftachul; Mun’im, Abdul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The activity of mentoring the use of writing tools aims to provide understanding and training to the students of Pondok Pesantren Sunan Drajat in compiling articles and scientific papers. The mentoring method is through workshop activities and practice compiling articles using the writing tools application. The implementation of the assistance was carried out on May 1, 2024 which was attended by 20 mahasantri. The result of the service is the realization of the understanding and ability of the assisted participants in preparing articles using a set of writing tools applications. In conclusion, the participants can use the writing tools application in preparing articles and scientific papers.